Modelling the impact of plain packaging of tobacco products on cardiovascular disease in Argentina - Salgado, Maria Victoria (2021)
Introduction Tobacco packaging design is conceived to be attractive. Plain packaging of tobacco products reduces this attractiveness by standardising their shape, size, font and colours. Methods To evaluate the effect of applying plain packaging to tobacco products on cardiovascular events and mortality in Argentina, we used the Cardiovascular Disease Policy Model-Argentina, a local adaptation of a well-established computer simulation model that projects cardiovascular and mortality events for the population 35-94 years old using local demographic and consumption data, during the period 2015-2024. After a literature review, we estimated that the implementation of plain packaging of tobacco products would result in an absolute decrease in tobacco prevalence of 0.55% (base-case scenario) and performed a sensitivity analysis assuming a higher and lower decrease of 1.01% and 0.095%, respectively. Results Over the 2015-2024 period, the decrease in smoking prevalence associated with plain packaging (0.55%) is projected to avert 1880 myocardial infarctions (MI), 820 strokes and 4320 total deaths in Argentina. The higher estimate of smoking prevalence reduction (1.01%) would translate into 3450 fewer MIs, 1490 fewer strokes and 7920 fewer deaths, while the lower estimate of smoking prevalence reduction (0.095%) would result in 330 fewer MIs, 140 fewer strokes and 750 fewer deaths. Conclusions The implementation of plain packaging of tobacco products could reduce cardiovascular events in Argentina, even in the absence of other tobacco control measures. Actual health benefits are likely higher than those presented here, since plain packaging may be most impactful by preventing young people from initiating smoking.